Identificação de progênies indutoras de haploidia em milho usando diferentes estratégias - Rodrigues, Paula Klotz Brandão (2019)
In maize, the success of a breeding program depends on the development of elite lines for the production of hybrids. An alternative to improving the efficiency of improvement programs, in order to reduce costs and time in the production of lines, is the use of double haploid technology. The success of double haploid lines production, depends on high induction rates and efficient identification of the true haploids. The in vivo haploid induction system, has become the major tool in haploid production in the crop. The objective of this study was to recombine the haploid inducers progenies of UFLA’s plant breeding and genetics program, to select the progenies with the highest percentages of induction, to identify haploids by the R-Navajo morphological marker and by flow cytometry , and also to verify if it is possible to identify individuals inducers haploid using molecular markers. The experiments were carried out in Lavras-MG. In the 2017/18 crop, S2: 5 progenies were recombined and self-fertilized. Inducers were crossed with the single hybrids P30F90, MG580, 2B810, 30A37, 2B640, 2A620, 2A401. The seeds obtained were assessed in relation to the morphological marker, 196 seeds with purple endosperm and white embryo were selected as possible haploids. The seeds selected as possible haploids were germinated in a greenhouse and submitted to flow cytometry to confirm ploidy. The calculation of induction rates was done considering haploids confirmed by flow citometry. DNA from 48 progenies was extraced, submitted to PCR and observed on 1% agarose gel. No fragment was amplifyed by primer. It was observed that the phenotypic manifestation of the R1-Navajo morphological marker is not precise. Therefore, it is necessary to study and improve the methodologies used to identify haploid individuals in order to ensure more accurate results on in-duction rates.